Increasing Teacher Performance Through Individual Supervision Of Teachers Of Sdn Gandasari 3 Tangerang City - Ade Fathurohman (Journal Of Social Science (JoSS), 2022)
This research is entitled: "Improving Teacher Performance Through Individual Supervision of Teachers at SDN Gandasari 3 Tangerang City".The purpose of this study was to improve teacher performance through individual supervision of teachers at SDN Gandasari 3 Tangerang City.The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and Reflection.Based on the results of action research that individual supervision can improve teacher performance at SDN Gandasari 3 Tangerang City.Furthermore, the researcher recommends: (1) For principals who experience the same difficulties, they can use individual supervision as a solution.(2) In order for the implementation of Individual Supervision to get maximum results, it is expected that the Principal will carry out Individual Supervision intensively and continuously.